Directed motion of liquid crystal skyrmions with oscillating fields. (1st March 2022) - Duzgun, A; Nisoli, C; O Reichhardt, C J; Reichhardt, C
Abstract: Using continuum simulations, we show that under a sinusoidal electric field, liquid crystal skyrmions undergo periodic shape oscillations which produce controlled directed motion. The speed of the skyrmion is non-monotonic in the frequency of the applied field, and exhibits multiple reversals of the motion as a function of changing frequency. We map out the dynamical regime diagram of the forward and reverse motion for two superimposed ac driving frequencies, and show that the reversals and directed motion can occur even when only a single ac driving frequency is present. Using pulsed ac driving, we demonstrate that the motion arises due to an asymmetry in the relaxation times of the skyrmion shape. We discuss the connection between our results and ratchet effects observed in systems without asymmetric substrates.